Assessment of balance, gait, lower limb strength and functionality in sarcopenic and non-sarcopenic elderlies - Magalhães, Alice Martins; Cerceau, Daniella Macedo; Parreiras de Menezes, Kênia Kiefer; Oliveira, Gabriela Vieira; Gomes, Bárbara Batista (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Sarcopenia is the involuntary loss of muscle mass predicted by aging and is associated with an increased likelihood of unfavorable results, such as falls, mortality and functional disabilities. Objective: Evaluate balance, gait speed, lower limb strength and functionality in sarcopenic and non-sarcopenic elderly. Methods: Cross-sectional study, carried out with 68 subjects aged 60 years or over, residents of the community and possessing an independent gait. The assessment instruments were bioimpedance, balance test, four-meter gait speed test, chair support test and SPPB. Results: The prevalence of sarcopenia in the population of the present study was 43.3%. In the group of non-sarcopenic subjects, a correlation was found between all the variables evaluated. In the group of sarcopenic subjects, a correlation was found between lower limbs strength and gait speed. Conclusion: The skeletal muscle mass of a sarcopenic elderly is related to their lower limb strength and gait speed, but it does not present a significant correlation with balance and functional performance. Further studies are needed to clarify the behavior of balance, gait speed, lower limb strength and functional performance variables when compared to the decrease in muscle mass inherent in aging.